Metaphors of Spain : representations of Spanish national identity in the twentieth century - Moreno Luzón, Javier; Núñez Seixas, Xosé M. (Xosé Manoel), 1966- (Studies in Latin American and Spanish history, 2017)
"The history of twentieth-century Spanish nationalism is a complex one, placing a set of famously distinctive regional identities against a backdrop of religious conflict, separatist violence, and the autocratic rule of Francisco Franco. And despite the undeniably political character of that story, cultural history can also provide essential insights into the subject. Metaphors of Spain brings together leading historians to examine Spanish nationalism through its diverse and complementary cultural artifacts, from 'formal' representations such as the flag to music, bullfighting, and other more diffuse examples. Together they describe not a Spanish national 'essence, ' but a nationalism that is constantly evolving and accommodates multiple interpretations"--Provided by publisher.